Поширеність і форми неплідності корів фермерського та присадибних господарств - Скляров, Павло Миколайович; Sklyarov, Pavlo; Sklyarov, Pavel; Sklyarov, P. M.; Skliarov, P. M.; Sklyarov, P.; Skliarov, Pavlo; Skliarov, P.; Колесник, Я.; Kolesnyk, J.; Хомич, Я.; Homych, J. (Одеський ДАУ, 2023)
Встановлено, що поширеність неплідності серед корів дослідних господарств складає 14,2% (12,2- 17,7%). Найпоширенішими формами неплідності корів виявилися аліментарна – 33,7% (29,9- 38,2%) і симптоматична – 25,0% (23,6-26,2%), а найменш поширеною була експлуатаційна – 4,6% (3,4-5,6%). При цьому практично мало місце їх поєднання: аліментарна + симптоматична, експлуатаційна + стареча, експлуатаційна + симптоматична, стареча + симптоматична, кліматична + симптоматична та кліматична + експлуатаційна + симптоматична. Найчастіше неплідність реєстрували в осінньо-зимово-весняний період – 89,7% (88,8-91,4%), натомість влітку вона була на найнижчому рівні – 10,2% (8,5-11,1%). The purpose of the work was to determine the prevalence and forms of infertility in cows on farms and homesteads. The general prevalence of infertility among cows and its forms, seasonal dependence were determined. In order to diagnose forms of infertility, the conditions of keeping and operating animals, rations and completeness of feeding, the results of clinical and gynecological studies were analyzed. A total of 1382 cows were subjected to retrospective analysis of the last 10-year period: 503 at RogaKopyta farm, 879 at privately owned farms in the village of Dudchany. It was established that the prevalence of infertility among cows in farms and privately owned farms is on average 14.2% ‒ 17.7% and 12.2%, respectively. The most common forms of infertility were alimentary – 33.7% (respectively, 38.2% ‒ in farms and 29.9% ‒ in privately owned farms) and symptomatic infertility – 25.0% (23.6% and 26.2%). The prevalence of senile infertility was somewhat lower – 10.2% (12.1% and 7.9%) and climatic infertility – 9.2% (10.1% and 8.4%). The prevalence of artificial infertility was at the level of 7.7% (7.9% and 7.5%), and the least common was exploitative – 4.6% (3.4% and 5.6%). 9.7% of cases remained undiagnosed (9.0% and 10.3%). At the same time, the discovered forms of infertility are defined as leading factors, and in fact their combination takes place. That is, the following combinations practically took place: alimentary + symptomatic, operational + senile, operational + symptomatic, senile + symptomatic, climatic + symptomatic, climatic + operational + symptomatic. It was determined that infertility was most often registered in the autumn-winter-spring period – 89.7% (91.4% in farms and 88.8% in privately owned farms). In particular, this indicator was at the level of 35.2% (38.4% and 33.4%) in winter, 27.4% in autumn (28.6% and 24.4%) and 27.1% in spring (26.7% and 28.7%). On the other hand, in the summer period, the number of barren cows was at the level of 10.2% (8.5% and 11.1%).
Prevalence and forms of infertility in cows of farms and homesteads
Скляров Павло Миколайович https://orcid.org/0000-0002-4379-9583
Keywords: фермерські та присадибні господарства; farms and homesteads; корови; cows; поширеність та форми неплідності; prevalence and forms of infertility